К вопросу изучения зарубежного читателя Литовской Советской печати - Старкунайте-Юркувенене, Ванда (Knygotyra, 1981)
The Soviet Union keeps cultural relations with many foreign countries. A form of these relations is the propagation of the Soviet press abroad. The Lithuanian press as an integral part of the Soviet press circulates abroad and has its readers. It is possible to classify foreign readers of the Soviet Lithuanian press into two main groups. The 1st group consists of the readers who do not know the Lithuanian language and who can read the Lithuanian press either in Russian or in one of the foreign languages. They fall into two subgroups according to their interests: the first subgroup consists of the readers who want to learn about the country and they read the publications prepared by the “Gintaras” Editorial Board of the Publishing House “Mintis”. The second subgroup consists of the readers who have different professional interests: they read scholarly publications either in Russian or those publications which have summaries in foreign languages. The 2nd group consists of the readers who know the Lithuanian language and can read in Lithuanian. They are mainly Lithuanian emigrants or people of Lithuanian descent. As the data of the questionnaire which was given to 169 Lithuanians abroad shows they also fall into two subgroups: the first subgroup is made up by the people who read Lithuanian literature, bulletins, and other publications out of nostalgia or other subjective motives; the second subgroup consists of those who read learned publications out of their professional interests. Many foreigners who have learned the Lithuanian language also belong to this subgroup. The data of the questionnaire will make other socio-demographical investigations of the foreign readers of the Soviet Lithuanian press more effective.